RETRACTED: Influence Of Brand Image, Product Quality And Customer Loyality To Purchase Decision Of Amdk Brand Aqua Area Mampang - Niendy Rizkia Rachmadany; Herry Krisnandi; Kumba Digdowiseiso (Journal of Social Science, 2024)
The aim of this research is to find out how much influence brand image, product quality and customer loyalty have on purchasing decisions for Aqua brand AMDK in the Mampang area of South Jakarta. The population in this study are agents in the Mampang area, South Jakarta and the number is unlimited. The sample for this research consisted of 100 respondents. With purposive sampling techniques (consideration samples) and quota sampling (quota samples). The data collection method uses a questionnaire. The analysis technique used is multiple linear regression. The results of the analysis obtained the regression equation Y = 2.611 + 0.199 X1 + 0.094 X2 + 0.137 X3. Based on the analysis and discussion, it is recommended that companies continue to maintain brand image, product quality and increase customer loyalty in accordance with consumer needs and desires as well as carry out new innovations in terms of promotions.